Maresin 1, a Proresolving Lipid Mediator, Ameliorates Liver Ischemia-Reperfusion Injury and Stimulates Hepatocyte Proliferation in Sprague-Dawley Rats - Soto, Gonzalo (Int J Mol Sci, 2020)
Maresin-1 (MaR1) is a specialized pro-resolving mediator, derived from omega-3 fatty acids, whose functions are to decrease the pro-inflammatory and oxidative mediators, and also to stimulate cell division. We investigated the hepatoprotective actions of MaR1 in a rat model of liver ischemia-reperfusion (IR) injury. MaR1 (4 ng/gr body weight) was administered prior to ischemia (1 h) and reperfusion (3 h), and controls received isovolumetric vehicle solution. To analyze liver function, transaminases levels and tissue architecture were assayed, and serum cytokines TNF-α, IL-6, and IL-10, mitotic activity index, and differential levels of NF-κB and Nrf-2 transcription factors, were analyzed. Transaminase, TNF-α levels, and cytoarchitecture were normalized with the administration of MaR1 and associated with changes in NF-κB. IL-6, mitotic activity index, and nuclear translocation of Nrf-2 increased in the MaR1-IR group, which would be associated with hepatoprotection and cell proliferation. Taken together, these results suggest that MaR1 alleviated IR liver injury, facilitated by the activation of hepatocyte cell division, increased IL-6 cytokine levels, and the nuclear localization of Nrf-2, with a decrease of NF-κB activity. All of them were related to an improvement of liver injury parameters. These results open the possibility of MaR1 as a potential therapeutic tool in IR and other hepatic pathologies.